THE INFLUENCE OF CURRICULUM RELEVANCE AND TEACHER COMPETENCE ON STUDENT SATISFACTION AT PKBM ANANDA BAIK ISLAMIC SCHOOL CIANJUR - Ramdhan, Muhammad (BAIK Publishers, 2025)
This study aims to analyse the influence of curriculum relevance and teacher competence on student satisfaction at PKBM Ananda Baik Islamic School in Cianjur, Indonesia. Using a quantitative explanatory design, the research involved 50 students from Paket A (elementary equivalency), Paket B (junior high equivalency), and Paket C (senior high equivalency) in the 2025/2026 academic year, selected through accidental sampling. Data were collected using questionnaires measuring curriculum relevance, teacher competence, and student satisfaction, and were analysed through correlation tests, coefficients of determination, t-tests, and F-tests. The findings show that curriculum relevance has a significant effect on student satisfaction, with a correlation coefficient of ???? = 0.563 and ????2 = 0.317, while teacher competence also has a significant effect, with ???? = 0.621 and ????2 = 0.385. Simultaneously, curriculum relevance and teacher competence significantly influence student satisfaction, indicated by ???? = 0.656, ????2 = 0.431, and an F-value of 17.781 with a significance level of 0.000, suggesting that improvements in both variables jointly enhance student satisfaction at PKBM Ananda Baik Islamic School Cianjur.